Economic Resilience of SME Businesses in Post-Crisis Lebanon: Challenges, Strategies, and Opportunities for Entrepreneurs - Omar, Maha Hajj (Journal of Cultural Analysis and Social Change, 2025)
This study examines the determinants of business resilience in post-crisis Lebanon using a mixed-methods approach combining survey data (n=100) and eight semi-structured interviews. Quantitative results revealed that strategic adaptation, external support, preparedness, and innovation networks significantly enhance resilience, while internal factors showed limited impact. Qualitative insights further emphasized the importance of collaboration, government and financial assistance, and adaptive strategies in navigating crises. The findings validate all three hypotheses, offering both theoretical and practical implications for policymakers and entrepreneurs seeking to strengthen economic recovery mechanisms in fragile contexts.